ОСОБЛИВОСТІ РОЗПОДІЛУ МЕХАНІЧНИХ ВЛАСТИВОСТЕЙ ВИСОКОМІЦНОГО ЧАВУНУ ПО ПЛАВКАХ - Бубликов, В. Б.; Бачинский, Ю. Д. (National Academy of Sciences of Ukraine, Physical-Technological Institute of Metals and Alloys of NAS of Ukraine, 2018)
Data on the distribution of mechanical properties (tensile strength, elongation and impact strength) of nodular graphite cast iron modified in the ladle with the complex modifier ЖКМК-4Р (FeSiMg-Ca-4RE) are given in the article. The Gaussian curves are constructed and the scattering of 40 melts average test results and the mechanical properties distribution of all the tests (120 cast and annealed samples, respectively) are analyzed. Prospective directions of technology improving for increasing of ductile cast iron mechanical properties are indicated.